Secure voting system for elections. (13th June 2022) - El-Gburi, Jabbar; Srivastava, Gautam; Mohan, Senthilkumar
In this paper, we present a novel electronic voting system (EVS) for political and social elections based on known cryptographic schemes. In cryptography, the El-Gamal encryption system is an asymmetric key encryption algorithm which is based on Diffie-Hellman key exchange. We use the El-Gamal algorithm to generate and encrypt random keys for the voters. This scheme is designed in a way that the communication channels are anonymous and in the meantime privacy, eligibility and fairness are applied to the entire system. Encrypted receipt-free transactions are provided to the voters after they submit a vote successfully. Once the voters have completed voting, the voters can check on voting online using the encrypted receipt, their confirmed participation in the election. The voters will not be aware of the chosen candidate to prevent cheating and vote selling, common issues in elections these days. The name of the chosen candidate will be confidential. The proposed voting system efficiently gives the opportunity for people to vote via their own PCs/laptops, thus decreases the queues accumulated up at voting centres. In addition, it offers a highly dependable authentication approach by national ID or biometrically which leads to overcoming electoral fraud.